A Study of Normal Epidermal Melanocyte Distribution - Kai-Lv Sun; Wan Liu; Xiao-Man Gao; Min Yang; Jian-Min Chang (Wolters Kluwer Health, 2021)
Abstract. Objective:. To elucidate the epidermal melanocyte distribution according to sex, age, and body part with the goal of providing benchmark data for the diagnosis and therapeutic effect evaluation of pigmentary skin diseases. Methods:. Epidermal melanocytes and keratinocytes were assessed using direct immunofluorescence staining, and the melanocyte density and epidermal thickness were calculated. The obtained data were statistically analyzed using SPSS Version 20.0 software. An independent-samples t test was used to compare the data between two groups, while data among three or more groups were compared by one-way analysis of variance. Data correlations were evaluated using Pearson correlation analysis. Results:. Melanocytes were uniformly distributed among the keratinocytes in the basal layer, and the average ratio of melanocytes to keratinocytes was 1:7. Among them, the ratio in males was 1:6.5 and that in females was 1:7.4, with no significant difference (P = 0.127). The melanocyte density gradually declined as age increased; the ratio was 1:5.8 before 50 years of age without an obvious downtrend. The average melanocyte density was 1:7.9 within 51 to 65 years of age and 1:8.5 at >65 years of age, and the difference was statistically significant (P < 0.01). Obvious differences were found in the melanocyte density among different body parts; in descending order, these densities were as follows: face (1:4.0) >neck (1:5.1) >hip (1:5.7) >upper limb (1:7.4) >lower limb (1:8.3) >lower back (1:9.2) >thorax and abdomen (1:9.9). The melanocyte density was not related to the epidermal thickness. Conclusion:. The melanocyte density showed a declining trend with age and significantly changed after 50 years of age. The melanocyte density was associated with body part; specifically, the density in the face, neck, and hip was higher than that in the limbs and torso. However, the melanocyte density was not associated with sex or epidermal thickness.